The Effect of Corporate Re-branding on Purchase Intention through The Brand Image of PT Pelita Air Service - Nastiti, Dinda Maisya; Syavaranti, Nadya; Aruman, Akhmad Edhy (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2021)
PT Pelita Air Service or PT PAS is a subsidiary of PT Pertamina (Persero) in aviation. In 2018, PT PAS changed its company logo. It is one of the corporate re-branding strategies that aimed to create a good brand image to increase the various services' purchase intention. This study aims to determine the effect of corporate re-branding on purchase intention through the brand image of PT PAS. This study used a quantitative associative approach with the survey method. Based on the sampling method, namely purposive sampling, the survey was performed on 97 respondents who knew about PT PAS. The results showed a direct and significant impact between corporate re-branding on purchase intention through the brand image of PT PAS with 0.375. Meanwhile, the direct effect of corporate re-branding on purchase intention is -0.083. Brand image becomes a mediator between corporate re-branding in increasing its influence on purchase intention. This research is expected to be a reference for PT PAS in evaluating its corporate re-branding strategy to form a better brand image and subsequently increase purchase intention for the services it offers.